United States and Latin American Undergraduate Students’ Knowledge, Attitudes and Perception of Global Agricultural Issues - Sarahi Morales; Todd Brashears; Cindy Akers; Jaime Malaga; Gary Wingenbach (Journal of International Agricultural and Extension Education, 2017)
Global trends are demanding agricultural students have a broader perspective of agriculture and competitiveness and they become responsible global citizens. This study compared United States and Latin American undergraduate students’ knowledge, attitudes, and beliefs regarding international agricultural issues, as well as their attitudes about global citizenship. Overall, students’ results indicated a lack of knowledge regarding international agricultural issues, with only 3.6% obtaining a score above 60%. Students’ recorded positive attitudes and beliefs about international agricultural issues but had mixed feelings regarding global citizenship attitudes. Scores on all constructs were found to be significantly different between the studied academic institutions (p < .05). The stepwise multiple linear regression indicated the predictors of university of enrollment and students’ attitudes and beliefs about international agricultural issues were significantly related to their global citizenship attitudes: F (3, 1194) = 83.04, p = .01, explaining 17% of the variance in the model. The obtained results suggest students hold positive and open-minded attitudes and beliefs regarding international agricultural issues. These attitudes should be balanced by academic institutions with the knowledge needed by students to meet the demands of the agricultural industry. A global understanding can potentially enable future professionals to succeed in both local and global settings, and furthermore, help them become global citizens.
Keywords: international agricultural issues; global citizenship; knowledge; undergraduate education.